Construction of nursing-sensitive quality indicators for epilepsy in China: A Delphi consensus study. (April 2023) - Ma, Xueping; Li, Yinping; Li, Jinmei; Zhou, Dong; Yang, Rong
Highlights: Thirty-nine candidate NSQIs for epilepsy care were identified through a literature review, a cross-sectional survey and a qualitative study. Twenty-four NSQIs were finally identified through two rounds of e-Delphi studies conducted by a panel consisting of 27 experts. The NSQIs included three domains: nursing resource allocation, implementation of nursing care, and outcomes of patients with epilepsy. Abstract: Objective: The quality and safety of epilepsy care are of great importance because seizures are unpredictable. The aim of this study was to develop a set of nursing-sensitive quality indicators (NSQIs) for assessing and improving the quality of epilepsy nursing care in China. Methods: An international literature review, a cross-sectional survey and a qualitative study were conducted to identify candidate NSQIs for epilepsy care and compile a questionnaire. Then, two rounds of electronic Delphi studies were conducted with a panel of 27 independent experts to identify the final NSQIs for epilepsy. Results: Thirty-nine candidate NSQIs were extracted for the Delphi process. The recovery rates in the first and second rounds of expert consultations were 92.6% and 96.2%, respectively. The experts' authority coefficients of the two rounds were 0.876 and 0.878, respectively. The Kendall W value of the two rounds ranged between 0.094 and 0.200 ( p <0.001). Eight structure indicators, 9 process indicators and 7 outcome indicators that represented the following three domains were included in the set of NSQIs for epilepsy: nursing resource allocation, implementation of nursing care, and outcomes of patients with epilepsy. Conclusion: These NSQIs for epilepsy provide a primary foundation for monitoring and improving the quality of epilepsy nursing care in China. However, the effects of these indicators on improvements in epilepsy care and outcomes in patients need to be verified in clinical practice.